1987
DOI: 10.1002/eji.1830170304
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the alternative pathway of complement by human serum IgA

Abstract: In order to study the activation of complement by soluble aggregates of human polyclonal serum IgA, lysis of sheep erythrocytes (E) coated with several IgA preparations was used as a model. A complement nonactivating monoclonal mouse IgG1 against IgA was used to coat the cells. IgA, isolated from normal human serum, was aggregated by either N-succinimidyl 3-(2-pyridyldithio)propionate (SPDP), glutaraldehyde, carbodiimide or heating. Depending on the size of the aggregates, and on the method of aggregation, E c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 28 publications
7
107
0
2
Order By: Relevance
“…The classical pathway is activated by IC containing IgM or IgG that bind with low affinity to Clq through its globular heads (24). More recently, the alternative pathway of the complement system has been demonstrated to be activated by IgA-containing IC (25,26). The demonstration of IgG antibodies to Clq in the serum of SLE patients demonstrated that not only IC, but also low molecular weight immunoglobulins, are able to bind to Clq.…”
Section: Discussionmentioning
confidence: 99%
“…The classical pathway is activated by IC containing IgM or IgG that bind with low affinity to Clq through its globular heads (24). More recently, the alternative pathway of the complement system has been demonstrated to be activated by IgA-containing IC (25,26). The demonstration of IgG antibodies to Clq in the serum of SLE patients demonstrated that not only IC, but also low molecular weight immunoglobulins, are able to bind to Clq.…”
Section: Discussionmentioning
confidence: 99%
“…IgA was purified from pooled normal human serum (NHS) or recalcified donor plasma, as described by Hiemstra et al (16), with minor modifications. In brief, the majority of serum proteins were removed by dialysis against H 2 O, and precipitation by ZnSO 4 .…”
Section: Purification Of Human Igamentioning
confidence: 99%
“…Complement activation by IgA has been previously shown to involve the alternative, but not the classical complement pathway (16,17). No data are available concerning the possible involvement of the lectin pathway.…”
mentioning
confidence: 99%
“…C3 can be activated by the alternative pathway [8], which is initiated as a result of a spontaneous and continuous hydrolysis of C3 (tickover process). This results in the generation of C3b which can react with complement-binding surface molecules (e.g.…”
Section: Complement Activation Pathwaysmentioning
confidence: 99%
“…Several studies suggest that C3 bound to IgA confers a particular nephrotoxicity to the IgA1-containing immune material, leading to the hypothesis that this step is the crucial hit in the pathogenetic event cascade of IgAN [8,9,11]. A different efficacy of complement activation may modulate the glomerular inflammatory reaction and the final tissue damage, driving different renal outcomes.…”
Section: Complement Activation In Iga Nephropathymentioning
confidence: 99%